Recurrent respiratory diseases in practice of family physician and pediatrician: main issues (a literature review) - O. I. Lemko; S. V. Lukashchuk (Zaporožskij Medicinskij Žurnal)
The aim of the study – to analyze the professional literature and evaluate modern scientific trends concerning definition, peculiarities of etiopathogenesis, differential diagnosis and prevention of recurrent respiratory diseases (RRD) in the practice of family doctors and pediatricians.